The Senandung Asahan: From a Magical Ritual to Performing Arts in the Community - Datmi, Rezki Ridho; Ardipal, Ardipal; Lumbantoruan, Jagar; Syeilendra, Syeilendra (Indonesian Research Journal in Education |IRJE|, 2023)
The development of the Senandung Asahan tradition from magical rituals to performing arts involves understanding the causes of its evolution performing arts. This research result shows that this tradition still exists and has been evolving since 1980 among the Asahan people because it was always performed during magical events, such as when fishermen would go to sea by invoking the wind as a ritual to ensure a bountiful catch. Nowadays, the Senandung Asahan Tradition is rarely seen and has transformed into performing arts, and beliefs have waned. The factors influencing this transformation include sociological, philosophical, aesthetic, and identity-related factors. Sociologically, this tradition is now used for local community entertainment. Philosophically, the values embedded within the Senandung Asahan Tradition have become iconic symbols and distinct features of the predominantly Islamic community. Aesthetic factors are manifested through the uniformity of presentation, such as attire. Meanwhile, identity-related exhibits unique and shared identities within the tradition.